Runoff regime changes in German rivers due to climate change - Bormann, Helge (ERDKUNDE, 2010)
The runoff regime characterises the mean seasonal runoff variations of catchments. The knowledge of the regime type therefore contains information on the average seasonal variability in runoff and the main feeding mechanisms of rivers. In the last decades, environmental change has affected the runoff regimes of German rivers. Changes in precipitation patterns, snow periods and evaporation rates have influenced the runoff regimes, same as construction of dams and river regulation measures. This study systematically analyses gauge data of large rivers in Germany in order to identify changes in the runoff regime, mainly caused by climate change since middle of the 20th century. It is shown that the general runoff regime types (such as pluvial, nival and glacial) have not changed. However, the detailed characteristics of the runoff regimes (amplitude, time of extreme values of the Pardé coefficients) were considerably affected by environmental change.